Protein Consumption Program (PCP) dalam pencegahan stunting pada anak di masa pandemi corona virus disease 19 - Giri Susilo Adi; etik pratiwi; Steffy Putri Amanda (STIKes Surya Global Yogyakarta, 2021)
One of the health successes of a country is determined by the nutritional status of children under five. Stunting can cause in decreased productivity, increased risk of degenerative diseases and increased in the birth of babies with low birth weight in the future. Protein needs are very important to prevent stunting in children. This study is to determine the effect of protein consumption program on stunting prevention in children. This research was a type of pre-experimental research, namely by providing a protein-containing food program at Posyandu Steyarini, Sinduharjo Ngaglik District, Sleman Yogyakarta. This activity took place from February to March 2021. The data collection technique used monitoring the measurement of the child's body weight and height to determine the nutritional status of the child for a period of 8 weeks. There were 41 samples aged 3 months - 5 years, female 19 people (46.34%) and male 22 people (53.65%). The results showed that there was an influence in the provision of protein consumption program on body weight and nutritional status of children, namely with a value (p value: 0,000) but this program had no effect on the child's body length with a value (p value: 1,000). Conclusion: giving protein program can improve children's nutritional status and body weight to prevent stunting in children.